Potential Failure of the Australian CFC Rules in the Digital Economy - Allen, Christina (Thomson Reuters, 2018)
The controlled foreign company (CFC) regime operates to overcome the situation where resident investors defer or avoid paying tax on their foreign sourced income by retaining profits within their controlled companies abroad. However, its prescriptive approach is concerning as we enter the digital era. One of the features which raises this concern is that income is categorised in a particular manner, which is examined by this article with reference to various revenue models in the digital economy. It observes that the existing framework provides tax planning opportunities with the effect to undermine policy objectives. This deterrence is likely to spread out among multinationals and small taxpayers alike as digitalisation becomes a prerequisite for doing business in modern commerce. The article first explains two structural taxing principles and how they relate to fiscal benchmarks. It discusses the operation of Australia's CFC rules to understand how the capital import neutrality benchmark is applied to exempt certain income from Australian tax. It further identifies key terms that provide the basis for giving this exemption, which are applied to the digital economy to demonstrate the extent to which the CFC rules are ineffective. In concluding remarks, the author suggests possible remedies based on the observations made throughout this article, but emphasises the need for broader analysis taking into account different industries, emerging business models and the use of intangibles. The reform is necessary with clear policy objectives and the consideration of other areas of tax law.